Characterization of binding interaction between rice glutelin and gallic acid: Multi-spectroscopic analyses and computational docking simulation. (December 2017) - Dai, Taotao; Yan, Xiaoyan; Li, Qian; Li, Ti; Liu, Chengmei; McClements, David Julian; Chen, Jun
Abstract: Many foods contain mixtures of plant dietary proteins and polyphenols, but there is currently a relatively poor understanding of the nature of the interactions between these components. In this study, the interaction of rice glutelin (RG) and gallic acid (GA) was characterized by spectroscopic and molecular docking techniques. The intrinsic fluorescence of RG quenched after the addition of GA, indicating that an interaction occurred. Thermodynamic analyses indicated that the binding process was spontaneous and the main driving forces were hydrogen bonds and van der Waals forces. The surface hydrophobicity of RG decreased with increasing GA. Furthermore, synchronous fluorescence and circular dichroism spectra provided insights into micro-environmental and conformational changes of RG. In particular, there was a reduction of α-helix structure and an increase of β-sheet structure present in RG after the binding interaction. Finally, molecular docking analysis provided a visual representation of a single binding site where GA interacted with specific amino acid residues located in the active site of the RG. Graphical abstract: Highlights: The interaction between rice glutelin (RG) and gallic acid (GA) was characterized. RG-GA interactions led to fluorescence quenching and conformational changes. The major RG-GA interactions were hydrogen bonds and van der Waals forces. This study provides valuable insights into nutraceutical-protein interactions.